The Influence of Perceived Service Quality Dimensions on Patients Satisfaction - Santoso, Anita Sevira; Saputra, Riski Novian Indra; Oktisari, Puni; Bernarto, Innocentius (Journal La Sociale, 2024)
The purpose of this study was to examine perceived service quality dimensions consisting of ambience, staff attitude, trustworthiness, outcome quality, administrative procedure, clinical procedure, price and billing, waiting time, resource availability, and information availability on patient satisfaction at Rumah Sakit Keluarga Sehat Tayu. The research approach uses quantitative with a questionnaire as a data collection tool. The sampling technique in this study used purposive sampling which obtained 196 respondents. The results of the study explain that perceived service quality dimensions consisting of ambience, staff attitude, trustworthiness, outcome quality, administrative procedure, clinical procedure, price and billing, waiting time, resource availability, and information availability have a very significant effect on patient satisfaction at Rumah Sakit Keluarga Sehat Tayu.